Design and manufacture of Type i lightweight concrete bricks, composed of recycled aggregates from concrete demolition waste, banana trunk fiber and rice husk ash - Martinez, Rodriguez (2023)
The use of concrete bricks in buildings causes 12% of structural failures due to the structural overload generated by masonry walls made with this type of material. In this research, it was proposed to reduce the weight of Type I concrete bricks without affecting their resistance, for which materials such as banana fiber and concrete demolition waste were added to generate a reduction in the weight of the bricks due to to their properties. Similarly, rice husk ash is incorporated to maintain the resistance of the concrete bricks. Four dosages were designed (M0, M1, M2 and M3) with which the different concrete mixtures and bricks were prepared. Concrete control tests were carried out (settlement, temperature, and unit weight), additionally, hardened concrete tests were carried out (warping, absorption, dimensional variation, and weight of the units). In relation to the main objective of the research, the bricks made with the mixtures M0, M1, M2 and M3 obtained average weights of 3920.55 g, 3692.45 g, 3489.05 g and 3161.65 g, respectively. Regarding resistance, the bricks made with the mixture M0, M1, M2 and M3 reached an average resistance after 28 days of 52.46 kgf/cm2, 54.70 kgf/cm2, 48.38 kgf/cm2 and 19.84 kgf/cm2, respectively. Finally, it was determined that by replacing traditional materials such as natural aggregates with recycled elements such as RCD and the use of materials such as ash instead of cement, improvements in concrete designs can be achieved. As in the case of sample M1 (600 gr/cm3 of silver fiber, replacement of 50% RCD and 2.5% rice husk ash), which obtained an improvement in compression resistance and a weight reduction. with respect to the standard sample